Comparative Review of Metal Ferrites for Heavy Metals Adsorption in Water - Kuntjahjono, Mayang Fauziah; Napoleon, Sultan; Sarweswara, Wikrama; Pandia, Yoselyn Evangelina; Haqina, Zidni Aghna; Sasongko, Nugroho Adi; Nuha, Nuha; Rifai, Akhmad; Basuki, Rahmat (Indonesian Scholar Society, 2025)
Heavy metal contamination in water is one of the most critical environmental issues, posing direct threats to human health and ecosystems. Various methods have been developed to address this problem; however, adsorption remains the most effective technique due to its simplicity, low cost, and regenerability. In this context, ferrite based materials (MFe2O4) offer great potential as heavy metal adsorbents owing to their combined advantages of magnetic properties, chemical stability, large surface area, and easy separation under an external magnetic field. This review paper provides a systematic comparison of various types of metal ferrites (Ni, Mn, Co, Zn, Mg, Cu, and Nd) applied for the removal of heavy metal ions from water. The comparison covers their crystal structures, morphology, surface area, magnetic properties, adsorption capacity, as well as the isotherm models and kinetics underlying the adsorption process. The findings show that each type of ferrite possesses specific advantages and limitations. NiFe2O4 exhibits high structural stability, MgFe2O4 demonstrates high adsorption capacity but is susceptible to dissolution under acidic conditions, CuFe2O4 exhibits strong chemical affinity, and NdFe2O4 shows potential selectivity toward specific ions. Meanwhile, MnFe2O4 and CoFe2O4, particularly in composite forms such as MnFe2O4/biochar and CoFe2O4/FAU, stand out with adsorption capacities exceeding 400 mg/g, sufficient magnetic properties, and easy magnetic separation, making them the most promising candidates for water treatment applications. This paper provides a comprehensive understanding of the structure property function relationship of metal ferrites as selective, stable, and efficient adsorbent materials for heavy metal remediation in aquatic environments.